Pathologic fracture in childhood and adolescent osteosarcoma: A single‐institution experience. Issue 4 (5th November 2016) - Haynes, Lindsay; Kaste, Sue C.; Ness, Kirsten K; Wu, Jianrong; Ortega‐Laureano, Lucia; Bishop, Michael; Neel, Michael; Rao, Bhaskar; Fernandez‐Pineda, Israel
Abstract: Purpose: Pathologic fractures occur in 5–10% of pediatric osteosarcoma (OS) cases and have historically been considered a contraindication to limb salvage. Our purpose was to describe the radiographic features of pathologic fracture and examine its impact on local recurrence rates, functional outcomes, and overall survival. Methods: We retrospectively analyzed patients at our institution from 1990 to 2015 with pathologic fracture at diagnosis or during neoadjuvant chemotherapy. We selected a control group of 50 OS patients of similar age and gender without pathologic fracture from 1990 to 2015. Functional outcomes were scored using Musculoskeletal Tumor Society criteria. Chi‐square test was used for comparative analysis of groups. Results: Thirty‐six patients with 37 pathologic fractures form the study cohort. Of patients who received surgery, 18 of 34 patients with fracture underwent amputation compared to 8 of 48 patients in the nonfracture group ( P = 0.007). Indications for amputation in fracture patients were tumor size (n = 7), neurovascular involvement (n = 6), and tumor progression during neoadjuvant chemotherapy (n = 5). Only one patient (2.9%) in the fracture group who underwent limb salvage suffered local recurrence. Of patients who received neoadjuvant chemotherapy, 25 of 34 fracture patients showed poor histological response compared to 24 of 47 nonfracture patients ( P = 0.044). There was no statistically significant difference in overall survival ( P = 0.96). Functional outcomes were significantly lower in fracture patients (median = 17.5) than nonfracture patients (median = 24) ( P = 0.023). Conclusions: Radiographic features of pathologic fractures were highly variable in this population. Limb salvage surgery can be performed without increased risk of local recurrence. Patients with pathologic fracture suffer worse functional outcomes but no decrease in overall survival.